Obituary: Ba Joseph Kiwele - Mrs. E.M. Dougall - Tracey, Hugh (International Library of African Music, 1961)
The African Music Society, and African musicians everywhere have suffered a great loss this year (1961) in the sudden death of the composer Ba Joseph Kiwele in Elizabethville, Katanga. At the time of his death (it is understood from heart failure) he was Minister of Education in the Katanga Government of President Tshombe. The Society also records the death on July 9th, 1961, of Mrs. E. M. Dougall, who for many years has been a good friend of the African Music Society through her interest in and work for the Tom Osborn Memorial.
Keywords: Ethnomusicology; African Music